DESKRIPSI POLA RITEM TAGANING PENGIRING LAGU-LAGU POP BATAK TOBA DI LAPO TUAK DI KECAMATAN KOTO TANGAH KOTA PADANG - Atmadi Simanullang; Jagar Lumban Toruan; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2012)
The proposes of this research to (1) describe pattern Rythme Taganing as follower as as pop Batak Toba in tuak shop in sub district koto tangah in padang. The problem of this research is to describe pattern Rhythm Taganing as follow as song in tuak shop. (2) the type of this research is qualitative that used descriptive the technique of collecting data are taken from library research, transerpt, observasion, interview, taking picture, recording data in field research. (3) the result of this research is Taganing as instrument that used in tuak shop in pasir parupuk tabing. The other instrument were guitar, hasapi. The song played are Anak Medan, Boru Pangoaran, Patik Palimaon. The pattern is Taganing is followed with song Rythme that played. The function of rhythm to crea nice condition at playing song in tuak shop. Keywords: Rhythm Pattern, Toba Batak people, taganing, Lapo Tuak